Pasundan People's Party in Pasundan Countries 1947-1950 - Sugih Rachmat Pangersa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research entitled "The Gait of Pasundan People's Party in Pasundan State from 1947-1950". The main problem in this research is to get to know "How was the gait of the Pasundan people's party in the Pasundan state from 1947-1950?". The method used in this research is the historical method. Based on the results of this research, it can be explained about the background of the formation of the Pasundan People's Party, the role of the founding figures of the Pasundan People's Party and the actions of the Pasundan People's Party in the Pasundan State government. The author concluded that the formation of Patai Rakyat Pasundan was motivated by Suria Kartalegawa's desire to lead West Java and was assisted by the Dutch who also wanted to form a Federal State in Indonesia. Suria Kartalegawa as a founding figure played an important role in the formation of the Pasundan People's Party which later declared the Pasundan State. The activities of the Pasundan People's Party in the government of the Pasundan State which divided into two, the first one is the Pasundan State declared by Suria Kartalegawa and second one is the Pasundan State as a result of the West Java Conference. Suria Kartalegawa's version of the Pasundan State did not last long due to the lack of support from several elements of society, both from figures or the West Java community itself and was considered a counter-revolutionary movement. Then the Pasundan version of the West Java Conference led by Wiranatakusumah V produced three West Java conferences, in this period Suria Kartalegawa and his Pasundan People's Party were more active in the Pasundan State Parliament with stand more in the opposition side. The Pasundan People's Party fainted and disbanded itself following the disbandment of the Pasudan State in 1950 and the arrest of Suria Kartalegawa, and then West Java again became part of the Republic of Indonesia.